Isfahan, Iran: A Review Study on Substance Abuse Status in High School Studen (International Journal of Innovative Research in Engineering & Management, 2023)
Because adolescent substance abuse is  common, and research have shown that drugs usage is  primarily linked to the taking of cigarettes and alcohol, an early extensive study of substances misuse generality, that  includes cigarettes and alcohol consumption, would seem to  be the fundamental factor in avoiding and taking control of drug consumption. The purpose of this research was to look  at articles published in Iran over the previous decade that  looked at those researches on the use of drugs by the  students of high school. From 2001 to 2011, publications  regarding student drug use were obtained from national  databases, with seven papers on 14–19 year old high school  students being analyzed. Cigarettes and hookah were the  most often used substances, and then alcohol, hash, opium,  ecstasy, and heroin, according to the seven publications  analyzed. Opium and heroin use was four to five times  greater in Kerman than in other cities studied. The use of  drugs is quite common among the society's teenagers and  young people therefore, they need proper attention and  elicit and decisive response.
Keywords: Addiction; High School; Iranian Students; Prevalence; Substances Abuse